2005
DOI: 10.1002/cjoc.200591275
|View full text |Cite
|
Sign up to set email alerts
|

Heteropolyacid‐catalyzed Reaction of Epoxides with Ketones: Efficient Synthesis of 1,3‐Dioxolane Derivatives

Abstract: An efficient method for the preparation of 1,3-dioxolanes via the coupling of epoxides with ketones catalyzed by heteropolyacids at ambient temperature has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hydrolysis reactions proceeded with very good yields (>84 %) for acetonides 15 , 17 and 21 (entries 1, 2 and 5). Substrates 19 and 20 , however, were transformed into their corresponding diols in slightly lower yields (79 % for 12 and 81 % for 13 ), probably due to the high volatility of the starting acetonides [25,26] . It should be noted that neither of them required any further purification step by chromatography.…”
Section: Resultsmentioning
confidence: 97%
“…Hydrolysis reactions proceeded with very good yields (>84 %) for acetonides 15 , 17 and 21 (entries 1, 2 and 5). Substrates 19 and 20 , however, were transformed into their corresponding diols in slightly lower yields (79 % for 12 and 81 % for 13 ), probably due to the high volatility of the starting acetonides [25,26] . It should be noted that neither of them required any further purification step by chromatography.…”
Section: Resultsmentioning
confidence: 97%
“…). The dioxolane can be formed from glycol or epoxide . The glycol is formed by hydroxylation of the epoxide in the presence of residual water .…”
Section: Resultsmentioning
confidence: 99%
“…heteropoly acids, HBF 4 and montmorillonites) and Lewis acids (e.g. SnCl 4 , TiCl 4 , CuSO 4 and BF 3 .O(C 2 H 5 ) 2 ) have been used as catalysts . Shan et al reported the ketalization and acetalization of carbonyl compounds with diols catalyzed by a carbon‐based solid acid, affording an average yield of 93% .…”
Section: Introductionmentioning
confidence: 99%
“…The direct conversion of epoxides to the corresponding acetonides has been described with the use of different Lewis acid catalysts. Among the most recent catalysts, with various degrees of success in terms of yield and selectivity, are anhydrous SnCl 2 ,2 tin( IV ) tetraphenylporphyrin perchlorate,3 2,4,4,6‐tetrabromo‐2,5‐cyclohexadienone,4 bismuth( III ) salts,5 various titanium complexes,6 [(C 5 Me 5 )Ir(NaMe) 3 ],7 RuCl 3 ,8 CH 3 ReO 3 ,9 Cu(OTf) 2 ,10,11Er(OTf) 3 ,12 BF 3 · Et 2 O,13 LiBF 4 ,14 and heteropolyacids 15. Many of these catalysts are strong Lewis acids and are not suitable in the presence of other functional groups.…”
Section: Introductionmentioning
confidence: 99%